BIOAVAILABILITY AND MOLECULAR DOCKING PREDICTION OF SECONDARY METABOLITE OF Curcuma zedoaria AS POTENTIAL MPRO SARS COV-2 INHIBITOR - Amaliyah Dina Anggraeni; Nia Yuniar Fitriana Putri; Septia Devi Amalia; M. Artabah Muchlisin (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Almost all countries worldwide have been exposed to the COVID-19 pandemic, which can cause respiratory diseases. Therefore, it is necessary to identify and develop drugs for the treatment of COVID-19. White turmeric (Curcuma zedoaria) is very popular because it is effective as an anticancer and antiviral agent. This study used the in silico method to predict the secondary metabolite compounds contained in C. zedoaria as inhibitors of Mpro (main protease) SARS-CoV-2. Of the 30 secondary metabolite compounds identified, 26 compounds had good bioavailability prediction, and three compounds (curcumadiol, curcumin, and desmethoxycurcumin) were predicted to have potential as SARS-COV-2 Mpro inhibitors because they have low inhibition constants and numerous ligand-protein interactions. Curcumadiol have binding energy: -8.34 kcal/mol; pKi: 0.77 µM; hydrogen bond: Glu166, Thr190, and Gln192; and hydrophobic bond: Met165 and Gln189. Curcumin have binding energy: -8.28 kcal/mol; pKi: 0.85 µM; hydrogen bond: Leu141, Gly143, Ser144, and Thr190; and hydrophobic bond: Cys145, Met165, and Gln189. Desmethoxycurcumin have binding energy: -7.83 kcal/mol; pKi: 1.84 µM; hydrogen bond: Asp187, Thr190, and Gln192; and hydrophobic bond: Met165. Keywords: Curcuma zedoaria, SARS-CoV-2, bioavailability, molecular docking